THE ANALYSIS OF TYPES ILLOCUTIONARY ACTS IN “TANGLED” MOVIE - Dila Ramayanti; Leni Marlina (Universitas Negeri Padang, 2018)
In the study of language, what people do by saying something is called speech acts. Speech acts is not only found in everyday life but also in the film. This research concerns with speech acts produced by the main character in Shrek movie script. The aims of this research are to describe the types of speech acts are produced by the characters in animated of western movie entitled “Tangled”. Data of this research in the form of utterances that involved illocutionary acts used by each character in that movie which is taken from YouTube then classify them into categories of illocutionary acts based on Searle’s of theory. The types of research in this study are qualitative and quantitative research. Qualitative research is applied to analyze the data in the form of the text. Quantitative research is used to count the member of speech acts used by the characters in that movie to conclude which types of speech acts is dominantly used. Based on data analysis, found that there are four of illocutionary acts found in that movie; directives, representatives, expressives, and commissives. This study shows that the dominant speech acts used is directives which 44% of percentage. It indicates that the characters of the movie “Tangled” use directives because some of them want the other character to do something.